PERANCANGAN BUKU PROFIL DINAS KEHUTANAN PROVINSI SUMATERA BARAT - Liza yuliana, Heldi, Ariusmedi (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
The purpose of designing a media campaignin the form of a book of this profile are (1) Introduction to the general public so thatmotivates the community inpreserving forests, (2) Increase knowledge and awareness to preserve and conserve the forest to the community, (3) Introducing West Sumatra Forestry Department in the form of company profile that people get information about the importance of forests and how to preserve it, (4) Assist the forestry department will inform the implementation of the work program, (5) Socialize the importance of protecting forests to the community especially the city of Padang. This data is obtained from observations and interviews with agency staff Forestry. Data one is using swot analysis. SWOT analysis stands for English Language, "strength" /strengths, "weakness" /weaknesses, "chance" opportunities, and the "threat" of threats. Swot analysis used in this study because of SWOT is away to analyzethe data, analysis conducted to assess and re-assess the (re-evaluation) a matter that has been there and has previously been decided in order to minimize the risks that may arise.